Efektivitas Insektisida Kombinasi Simplisia Daun Tembakau, Srikaya dan Bandotan dalam Mengendalikan Ulat Tritip pada Tanaman Sawi - Arruan, Dini N.; Ahmad, Haeranah; Askur, Askur; Mappau, Zrimurti (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
The leaf-eating caterpillar pest Plutella xylostella or Tritip caterpillar mostly attacks vegetable plants of the Cruciferae family, one of which is mustard greens and causes around 12.5% ​​damage. Characteristics of damage to mustard plants due to tritip caterpillars are transparent spots on the leaves so that they become torn. This study aims to determine the effectiveness of the insecticide combination of simplicia from tobacco, srikaya and bandotan leaves in controlling barnacle caterpillars on mustard greens with variations in concentration and length of time. This research is an experimental research that uses simplicia methods and extraction by infusion. The test will be carried out in 3 repetitions with a concentration of 15%, 30%, 45%. The number of samples used for each concentration was 5 caterpillars and observed every 24 hours once in 3 days. It will be held in June 2023 at the Parasite Laboratory, Department of Environmental Health, Mamuju Ministry of Health Polytechnic and in Banggo Hamlet, Mamasa District, Mamasa Regency, West Sulawesi Province. Based on the data and results of the analysis that has been carried out, it is known that the simplicia extracts of tobacco, srikaya and bandotan leaves were tested one to the third with a concentration of 15%, namely 15g of the simplicia combination dissolved in 85ml aquadest, 30%, namely 30g simplicia dissolved in 75ml aquadest, 45% namely 45g of simplicia dissolved in 55ml of distilled water is very effective against the death of barnacle caterpillars (pulutella xylostella). The higher the concentration used, the higher the potential to kill tritip caterpillars. It is hoped that further research can develop the results of this study by carrying out further research, namely carrying out the observation process when testing extracts for the death of test animals at hourly time intervals and making work procedures that are more easily applied in the community.